2019
DOI: 10.1097/md.0000000000017058
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hyperthyroidism following the ingestion of complementary medications containing kelp seaweed

Abstract: Rationale:The prevalence of obesity has increased over the past few years, becoming a public health problem. Generally, the primary therapeutic remedies are diet, physical exercise, medication, and bariatric surgery. However, an increased number of obese and overweight people are using complementary and herbal slimming supplements.Patient concerns:A 70-years-old Caucasian woman presented to the outpatient clinic with tachycardia (>100 bpm), insomnia, anxiety, and recent weight loss (6 kilos in 3 months). She h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Further studies are required to examine thyroid function in macroalgae consumers with an excessive iodine intake. Previously, several case studies have reported iodine-induced thyroid dysfunction in adults consuming seaweed [ 42 , 43 , 44 , 45 ]. Thyroid dysfunction has also been seen in new-born babies after excessive maternal iodine intake from macroalgae [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to examine thyroid function in macroalgae consumers with an excessive iodine intake. Previously, several case studies have reported iodine-induced thyroid dysfunction in adults consuming seaweed [ 42 , 43 , 44 , 45 ]. Thyroid dysfunction has also been seen in new-born babies after excessive maternal iodine intake from macroalgae [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the findings of thyroid scintigraphy and thyroid color Doppler ultrasonography in previously reported cases of iodine-induced hyperthyroidism in patients without a history of thyroid disease (Table 1). [3,7,[10][11][12][13][14][15][16][17][18] Although many reports describe decreased radioiodine intake, [10][11][12]16] radioiodine uptake varies widely in cases of amiodarone-induced hyperthyroidism type 1. [6] In iodine-induced hyperthyroidism, color Doppler thyroid ultrasonography generally shows increased blood flow [6,14] ; however, cases without increased blood flow also exist.…”
Section: Discussionmentioning
confidence: 99%
“…Graves-Basedow disease is an autoimmune disease triggered by certain viral or bacterial infections (e.g., Yersinia enterocolitica), psychological stress, smoking, estrogen and postpartum period, excessive administration of iodine (especially in iodine deficient areas) or of drugs certain drugs such as Amiodarone (Gherbon et al, 2019). The manifestations of the disease include thyrotoxicosis, ophthalmopathy, goiter, dermopathy (pretibial myxedema).…”
Section: Discussionmentioning
confidence: 99%